Dampak Penerapan E-Recruitment Bagi Tenaga Kerja dan Perusahaan - Yunus Handoko; Zainul Muchlas (STIE Malangkucecwara, 2014)
Recruitment is important for organization because it has function of collecting human resources toward the organization, the technology development has grown up and it forces Company to apply what is called as e-recuitment which is internet based recruitment. There are some differences in this system compared to traditional recruitment system. However, the difference is not problem because company gain many advantages from the online system, which are cost efficiency, easy-to-use by candidate, easy-to-use by organization, increasing speed of recruitment process and the success of finding potential employees. Despite of the imperfect theory about the ideal implemention that company can implement the system successfully, some big companies like Microsoft, Oracle and Bank of Ireland e-recruitment system. Local and national companies such as Garuda Indonesia, PT. Pertamina, PT.Krakatau Engineering also implement this system.